Environmental education and the Ecoschool: Essential instruments for sustainable development (Research, Society and Development, 2022)
The beings that make up nature need to be in harmony, to together maintain the balance of the planet. In order to promote Environmental Education through ecological actions in an Ecoschool, an investigative form was applied to 44 adults. The results obtained through the applied forms demonstrate that that community is affected by the existing environmental problems in the area where they reside; being the "garbage" the environmental problem in the area of housing, and that the existing environmental problems affect their life. They also demonstrate the importance of Environmental Education, in order to add values about ecological actions that can be improved or expanded in the Ecoschool, involving that community and thus provide a better understanding of measures and actions that can be taken to minimize environmental problems in that area, because environmental education contributes to awareness, preservation, and environmental conservation of the planet.